WHATSAPP GROUP-BASED LEARNING ANALYSIS ON ACHIEVEMENT AND LEARNING DIFFICULTIES OF ELEMENTARY SCHOOL STUDENTS - Nuryanti; Nurdyansyah; Eni Fariyatul Fahyuni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to analyze WhatsApp group–based learning on the achievement and learning difficulties of elementary school students. The method used in this research is descriptive qualitative with a case study approach. The population of this study was elementary schools in Porong District, Sidoarjo Regency, selected through a purposive sampling technique from several informants. Informants consisted of teachers, parents of students, and students. Data collection in this study was carried out through (1) interviews, (2) observation, and (3) documentation. Data collected through interviews, observation, and documentation were then analyzed using inductive descriptive techniques. Data analysis was conducted through data reduction, data display, and data verification. The results of the study showed that an average of the three respondents agreed with WhatsApp-based learning as much as 28.5%, and those who disagreed were 71.48%. These results indicate that WA-based learning is not a problem to implement in elementary schools, but in its application, there are obstacles experienced by teachers, parents, and students, including the lack of facilities owned and students becoming bored with the learning process.